Magnetoelastic properties of terbium substituted cobalt ferrite - Bhame, Shekhar D.; Joy, Pattayil Alias (Chemical Physics Letters, 2017)
The magnetic properties of terbium substituted cobalt ferrites CoFe(2-x)TbxO(4) (x = 0, 0.05, 0.1, 0.15 and 0.2) prepared by conventional solid state method are studied. The coercivity showed marked increase up to x = 0.1 and saturation magnetization decreased with increasing terbium content. Magnetostriction measurements did not show much decrease in the maximum value of strain but significant increase in the slope of magnetostriction was observed for x = 0.15 with moderate magnetostriction of around 144 ppm. The observed magnetic and magnetostrictive properties can be explained on the basis of structural and microstructural changes arising because of terbium substitution. (C) 2017 Elsevier B.V. All rights reserved.

Magnetic and magnetoelastic properties of Ni-substituted cobalt ferrite - Bhame, Shekhar D.; Shirolkar, Mandar M.; Joy, Pattayil A. (IEEE Magnetics Letters, 2021)
In this letter, magnetic and magnetostriction studies were performed on spinel ferrite Co1-xNixFe2O4 (CNF series) with 0.0 < x < 0.5. All the samples were synthesized by the conventional ceramic method and confirmed to be forming pure spinel phase. The unit cell parameter showed gradual decrease with increasing Ni content. A linear decrease in saturation magnetization (M-s) and coercivity (H-c) was observed with increasing Ni substitution, which could be attributed to reduced magneto-crystalline anisotropy. The room temperature magnetostriction studies revealed a slow decrease in maximum magnetostriction, and interestingly, for 20% reduction of cobalt concentration, i.e., for x = 0.2, a magnetostrictive strain of -164 ppm and substantially high stress sensitivity of -56 x 10(-6) A(-1) m were observed, making Co0.8Ni0.2Fe2O4 suitable for application as a magnetostrictive stress-sensing material.
Keywords: Ferrite; Magnetism in solids; Magnetostriction; oxide; stress sensing